Unraveling the Untold Stories of University Students on Mental Health Struggles: An Exploratory Study - Bernardo K. Gumarang Jr. (CV. Literasi Indonesia, 2022)
The outbreak of the virus during this pandemic gave so many struggles in the different countries around the world which also shook the world economy. Universities are also affected since the outbreak started which brought changes to the way students live while they are pursuing their degrees in college. This study explored the psychological problems encountered by college students amid the pandemic. The study used descriptive phenomenology as its research design. The researcher invited nine students to participate in the study using purposive sampling. As part of the ethical considerations, the researcher used code names to hide the identity of the participants. Colazzi’s method of analysis was used by the researcher to identify the themes. This study revealed four themes related to students’ psychological problems which are Intense Power of Stress and Pressure, Battling with the spirits of Anxiety and Depression, Living in the Shadow of Death, and Fear of Uncertainty in Life. Based on the findings, the researcher recommends that the universities must actively guide their students by having mental health webinars, and most especially the guidance counselors must follow up with those students who are struggling mentally. The instructors must also give the utmost leniency to help the students cope with the adversities brought by this pandemic. Future researchers may also consider studying the challenges of students academically and their coping mechanisms.